Editorial: What’s in a Name? Distinguishing forced labour, trafficking and slavery - Piper, Nicola; Segrave, Marie; Napier-Moore, Rebecca (Anti-Trafficking Review, 2015)
Over the last fifteen years the parameters of anti-trafficking have shifted considerably. This shift has not been immediate or seismic. It has been a gradual shift, and what was once advocated for as a specific practice of trafficking is now associated with, and at times used interchangeably with, slavery and forced labour.